2014
DOI: 10.1016/j.sapharm.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Addressing medication nonadherence by mobile phone: Development and delivery of tailored messages

Abstract: Background: Medication nonadherence remains a significant public health problem, and efforts to improve adherence have shown only limited impact. The tailoring of messages has become a popular method of developing communication to influence specific health-related behaviors but the development and impact of tailored text messages on medication use is poorly understood. Objectives: The aim of this paper is to describe an approach to developing theory-based tailored messages for delivery via mobile phone to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…The use of individually tailored information has been shown to be effective in promoting beneficial health behavior changes in adults in other contexts as well. 29,30,31 Although text messaging has been the most popular tool for facilitating behavioral interventions towards effective chronic disease self-care support, only a small percentage of American adults living with chronic diseases receives the benefits of text messaging for their health care support. 32,33,34 With advances in mobile health services and the widespread use of mobile phones in the Asian American population and in other ethnic minority populations, text messaging may be a powerful, costeffective way to facilitate communication between the patients and health care personnel, thereby improving health literacy and care disparity in ethnic minority populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of individually tailored information has been shown to be effective in promoting beneficial health behavior changes in adults in other contexts as well. 29,30,31 Although text messaging has been the most popular tool for facilitating behavioral interventions towards effective chronic disease self-care support, only a small percentage of American adults living with chronic diseases receives the benefits of text messaging for their health care support. 32,33,34 With advances in mobile health services and the widespread use of mobile phones in the Asian American population and in other ethnic minority populations, text messaging may be a powerful, costeffective way to facilitate communication between the patients and health care personnel, thereby improving health literacy and care disparity in ethnic minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…These results are congruent with the results of other studies on chronically ill patients, which have demonstrated high levels of receptivity and satisfaction. 29,30 Limitations of the study We recognize that there are some limitations in our study. First, the sample size (n=32) is small, and the participants in this study may not be representative of the overall Korean American or other ethnic minority populations in the United States.…”
Section: Diversity Of Message Themesmentioning
confidence: 92%
“…The tailoring of diabetes-specific text messages remains an area of opportunity to improve medication adherence and provide motivation to adults with diabetes but further research is needed to fully understand their effectiveness. Personalized text advices have proven to produce a positive impact on patients' empowerment, self-management, and adherence to prescriptions (Gatwood et al 2014). mHealth can be used for offering self-management support programs to diabetes patients and at the same time surmounting the technical and financial difficulties involved in diabetes treatment (Free et al 2013).…”
Section: XXXVIIImentioning
confidence: 99%
“…Sin embargo, se necesita más investigación para entender totalmente su eficacia. Los consejos de texto personalizados han demostrado causar un impacto positivo en la atribución de poder a los pacientes, su autogestión y su adherencia a la prescripción (Gatwood et al, 2014). mHealth se puede utilizar para ofrecer programas de asistencia de autogestión a los pacientes con diabetes y, al mismo tiempo, superar las dificultades técnicas y financieras que supone el tratamiento de la diabetes (Free at al., 2013).…”
Section: La Motivación Y Atribución De Poder De Los Pacientes Son Quiunclassified
See 1 more Smart Citation